Study on Aberrant Eating Behaviors, Food Intolerance, and Stereotyped Behaviors in Autism Spectrum Disorder - Li, Chunyan; Liu, Yang; Fang, Hui; Chen, Yu; Weng, Jiao; Zhai, Mengyao; Xiao, Ting; Ke, Xiaoyan (Frontiers in Psychiatry, 2020)
Objective: To investigate the aberrant eating behaviors (EBs), gastrointestinal (GI) symptoms, and food intolerance in children with autism spectrum disorder (ASD) and their association with core symptoms of ASD. Method: A total of 94 preschool children with ASD treated at the Child Mental Health Research Center of Nanjing Brain Hospital between October 2016 and April 2018 were enrolled. In addition, 90 children with typical development (TD) in the community during the same period were recruited. The conditions of aberrant EBs and GI symptoms in children were investigated using questionnaire surveys. Serum specific IgG antibodies against 14 kinds of food were detected using enzyme-linked immunosorbent assays (ELISAs). Results: The detection rate of aberrant EBs in the ASD group was significantly higher than that in the TD group (67.39% vs 34.94%), and the rate of GI symptoms was also higher in the ASD group than that in the TD group (80.22% vs 42.11%). Detection of food intolerance in children with ASD showed that the positive rate was 89.89% and that the majority of children had multiple food intolerances. The correlation analysis results showed that the severity of aberrant EBs positively correlated with stereotyped behaviors of children with ASD (r=0.21, p=0.04) and that food-specific IgG antibodies concentrations positively correlated with high stereotype levels in children with ASD (r=0.23, p=0.03). Conclusion: ASD with aberrant EBs or high food-specific IgG antibodies concentrations had more severe stereotyped behaviors, these results suggest that ASD might be an immune-mediated behavioral syndrome.